Kewirausahaan Sosial di Muara Teweh: Membangun Ekonomi Komunitas Melalui Inovasi dan Kolaborasi yang Berkelanjutan - Ahmad Fahrizal; Hastin Umi Anisah; Mahdi Hidayatullah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study explores social entrepreneurship in Muara Teweh, focusing on how innovative practices and collaborative efforts contribute to community economic development. The research employs a Systematic Literature Review (SLR) methodology to analyze existing literature related to social entrepreneurship and its impacts on local economies. By examining various case studies and theoretical frameworks, this paper identifies key factors that facilitate successful social entrepreneurial initiatives in Muara Teweh. The findings reveal that innovation and collaboration not only enhance the effectiveness of social enterprises but also foster sustainable economic growth in the community. This study highlights the importance of integrating local resources and knowledge, as well as the role of community engagement in driving social entrepreneurship forward. The research concludes with recommendations for policymakers and practitioners to enhance the effectiveness of social entrepreneurship in Muara Teweh, emphasizing the need for supportive frameworks that encourage innovation and collaboration among stakeholders.